2019
DOI: 10.12659/msm.914725
|View full text |Cite
|
Sign up to set email alerts
|

Independent Clinical Factors Relevant to Prognosis of Patients with Idiopathic Pulmonary Fibrosis

Abstract: Background The prognosis of idiopathic pulmonary fibrosis (IPF) is the worst among all interstitial lung diseases, and is related to the disease itself. Comorbidities or complications can worsen IPF. We assessed the effect of comorbidities on the survival of IPF patients. A retrospective review of patients with IPF was completed. Material/Methods Information on demographic features, clinical examination, and comorbidities at baseline were obtained. Then, median, 1-year,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…A link between ATIII and neutrophil activity can be supposed irrespective of coagulation cascade regulation, because ATIII interacts with cell mediators of inflammation, which are mainly produced by neutrophils 22,23 . Polymorphonuclear cells are involved in fibrotic mechanisms in the lung and increased percentages of neutrophils have been demonstrated in BAL and tissues of IPF patients 24,25 . Interestingly, we found significant correlations between ATIII concentrations and pulmonary function test parameters, which strongly suggest the potential prognostic value of ATIII in the pathogenesis of IPF.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…A link between ATIII and neutrophil activity can be supposed irrespective of coagulation cascade regulation, because ATIII interacts with cell mediators of inflammation, which are mainly produced by neutrophils 22,23 . Polymorphonuclear cells are involved in fibrotic mechanisms in the lung and increased percentages of neutrophils have been demonstrated in BAL and tissues of IPF patients 24,25 . Interestingly, we found significant correlations between ATIII concentrations and pulmonary function test parameters, which strongly suggest the potential prognostic value of ATIII in the pathogenesis of IPF.…”
Section: Discussionsupporting
confidence: 50%
“…22,23 Polymorphonuclear cells are involved in fibrotic mechanisms in the lung and increased percentages of neutrophils have been demonstrated in BAL and tissues of IPF patients. 24,25 Interestingly, we found significant correlations between ATIII concentrations and pulmonary function test parameters, which strongly suggest the potential prognostic value of ATIII in the pathogenesis of IPF. ATIII levels in serum were also directly correlated with BAL neutrophil percentages and both parameters seem reliable predictors of poor survival.…”
Section: Discussionmentioning
confidence: 55%
“…In the present study, elderly people (> 65 years) did not have a worse prognosis than young people (≤ 60 years). While Song et al [29] reported that younger patients (< 50 years) tended to have a good prognosis compared to that of elderly patients (> 75 years), the difference was not significant (Kolmogorov-Smirnov test, p = 0.268). One potential reason for this difference is due to nintedanib's high frequency of side effects (e.g., diarrhea, anorexia, liver injury) [10].…”
Section: Discussionmentioning
confidence: 82%
“…In the original report of the GAP system by Ley et al [19], sex had a lower impact on prognosis compared with other factors. Although mortality due to IPF was initially reported to be higher in men [12], a recent study by Song et al [29] found that among 380 patients with IPF, survival time was nearly equivalent between male (46.6 months) and female (45.0 months) patients (Chi-squared test, p = 0.887). These findings are consistent with the outcome of our study and together suggest that the administration of nintedanib does not affect the relationship between gender and prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of comorbidities with IPF can significantly influence the prognosis. Song et al (24) and Cai et al (27) showed in their studies that PAH was associated with a poor outcome. Distance walked in 6 min was independently related to mortality by multivariate analysis in Caminati and coworkers' study (28).…”
Section: Resultsmentioning
confidence: 96%